Pediatric Urology Evidence for Optimal Patient Management - Snodgrass, Warren T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Pediatric Urology: Evidence for Optimal Patient Management provides pediatric urologists the information needed for state-of-the-art patient care. Chapters are organized around pertinent clinical questions within major areas of pediatric urology, answered using the best available data while also reporting areas for which there is poor evidence. The text includes randomized controlled trials and prospective observational studies, tables that summarize important studies, and figures that illustrate algorithms with best options for management and their expected results. With an easy to use format not found in other volumes, Pediatric Urology: Evidence for Optimal Patient Management is an indispensible and unique resource for experienced pediatric urologists, pediatric surgeons, general urologists with an interest in pediatric urology, as well as fellows and residents in training.
Urinary Tract Infection -- Vesicoureteral Reflux -- Bladder and Bowel Dysfunction -- Nocturnal Enuresis -- Undescended Testes -- Hernias and Hydroceles -- Testicular Torsion -- Varicocele -- Hypospadias -- Phimosis, Meatal Stenosis, and BXO -- Ureteropelvic Junction Obstruction -- Multicystic Dysplastic Kidney -- Ureteroceles and Ectopic Ureters -- Non-Refluxing Megaureter -- Posterior Urethral Valves and Ureterovesicojunction Obstruction -- Neurogenic Bladder -- Urolithiasis.
Keywords: Medicine; Surgery; Urology; Medicine & Public Health; General Surgery; Urology/Andrology.